Fantasizing history between subjectivity and objectivity - Asem Baniamer; Noor Issa Allendi (Cogent Arts & Humanities, 2024)
This research delves into the intricate interplay between subjectivity and objectivity within the context of historical fantasizing. It also explores the potential for a symbiotic relationship between narrative and history to generate empirical literature that anticipates and aligns with future developments, despite the apparent contradictions inherent in these two disciplines: history, characterized by its objectivity, and narration, characterized by its subjectivity. To accomplish this objective, the study meticulously scrutinizes the mechanisms facilitating the fusion of narrative and history. It also conducts a thorough examination of subjectivity within both historical and narrative contexts, utilizing the concept of fantasizing as a lens through which to explore its connection to narration. Furthermore, the study investigates the roles of narrators and historians, identifies points of convergence and divergence between them, and sheds light on potential challenges arising from the tension between subjectivity and objectivity in their respective domains.